Proposed Spray System for Family Agriculture with A Remote-Controlled UAV (Small Drone or Helicopter) and An Economical Sprinkler - Cuauhtémoc Negrete Jaime (Journal of Agronomy Research, 2020)
In the country, food production is more compromised every day, despite zero efforts and government, agricultural and livestock sector, causing poverty, migration, marginalization among other social disorders in addition to food insecurity. In Mexico 34% of the population is engaged in agricultural tasks, with very small land areas. The fact that 85% of do not have more than 5 ha of arable land, and that among them, 90% do not reach 3 ha clearly indicates their great need for light machinery .The solution to these problems family farmers are provided with affordable technologies to increase their productivity. One of the most common problems in agriculture is the application of agrochemicals, which is tedious and dangerous when farmers are exposed to these highly toxic products, therefore a system is proposed is through the help of a drone or remote control helicopter, both of economic type connected by a hose to the sprinkler and a tank. Due to the danger of applying agrochemicals for family farmers who rarely follow the precautions to apply these products, the proposed alternative is attractive for small agricultural properties, although it is not free of cost, the drone and the optimal sprayer should be investigated.
Keywords: Agriculture